Fitness and psychological effects of tele-exercise in healthy populations. Preliminary study - Fucarino, Alberto; Zimatore, Giovanna; Fabbrizio, Antonio; Garrido, Nuno D.; Reis, Victor Machado; Vilaça-Alves, José; Sausa, Martina; Matteo, Barbara; Peixoto, Rafael; Perušina, Paulina; Aristova, Aleksandra; De Giorgio, Andrea; et al. (Frontiers in Digital Health, 2024)
BackgroundThe study investigates the impact of tele-exercise on physical fitness and psychological well-being in healthy individuals. Tele-exercise, facilitated by technology, offers a flexible and accessible alternative to traditional exercise, particularly beneficial during restricted in-person interactions.MethodsIn this study, 52 participants were divided into three groups: athletes, women, and young adults. They took part in an eight-week tele-exercise program, either synchronously or asynchronously. Physical fitness was evaluated using tests such as the 2-Minute Step and Curl Up Test, while psychological well-being was assessed using the Psychological General Well-Being Index (PGWBI) and Perceived Stress Scale (PSS-10).ResultsSignificant improvements in physical fitness and psychological well-being were observed in post-intervention across all groups, regardless of training mode. In the fitness tests, a significant improvement was obtained in the 2-Minute-Step (p = 0.004), in the curls up (p = 0.017), and in squats test (p = 0.004). In the forward bending test, the increment was very close to the significance (p = 0.051). In the psychological well-being tests, both PGWBI and WHO-5 scores increased after the training (p = 0.024 and p = 0.001 respectively) with no significant change in the PSS-10 score. The study found that tele-exercise can effectively introduce physical activity to previously inactive individuals and motivate them to adopt healthier lifestyle behaviors.ConclusionsThe TELEexe4ALL project demonstrates the potential of tele-exercise to improve physical fitness and psychological well-being. The study suggests that tele-exercise is a feasible and well-accepted approach for enhancing overall wellness in healthy populations.